Holmium Laser Prostatectomy for Primary Bladder Neck Obstruction (PBNO): Comparative Efficacy and Safety Outcomes versus Benign Prostatic Hyperplasia (BPH): Holmium laser prostatectomy in PBNO vs BPH - Al-Rawashdah, Samer; Ayyad, Malik; Ayaad, Omar; Abu Zahra, Khalil; Al Demour, Saddam; Al-Zubi, Mohammad (Journal of Lasers in Medical Sciences, 2025)
Introduction: Holmium laser prostatectomy (HoLEP) is widely used for benign prostatic hyperplasia (BPH), though primary bladder neck obstruction (PBNO) is less commonly recognized despite similar symptoms. Treatment outcomes can vary, especially when diagnosis is delayed, but the condition is sometimes not very different from BPH. The purpose of this study was to compare PBNO patients with those undergoing surgery for BPH, even though PBNO is not always treated surgically. Methods: A total of 79 men from three hospitals in Jordan (PBNO=30, BPH=49) were reviewed retrospectively. They all received HoLEP regardless of individual suitability or prior diagnostic clarity. Data were collected through symptom scoring (IPSS, OABSS), but not all patients completed the follow-ups equally. Results: While patients with PBNO showed symptom improvement after surgery, the improvements were not always significant or clearly linked to the procedure itself. Interestingly, PBNO patients had shorter surgeries (27.2 vs. 60.5 minutes, P<0.01), though it is unclear whether that impacted recovery. Despite reporting fewer complications, their satisfaction was lower (64.3% vs. 93.8%, P=0.09), perhaps due to reasons not directly assessed in the study. Repeated Measures ANOVA revealed a statistically significant improvement in IPSS scores over time in both groups: PBNO (F(2.1, 58.4)=16.8, P<0.001) and BPH (F(2.4, 116.8)=21.3, P<0.001). Similarly, OABSS scores showed a significant improvement over time for both PBNO (F(2.6, 74.0)=8.9, P<0.001) and BPH (F(2.8, 134.2)=9.7, P<0.001). Conclusion: HoLEP appears effective for PBNO, though it may not be the most suitable approach in all cases. Since PBNO differs from BPH, further studies might be needed, or perhaps not, depending on patient variability.